KEPALA SEKOLAH SEBAGAI PEMIMPIN PERUBAHAN DI SEKOLAH MENENGAH KEJURUAN UNTUK MENDUKUNG IMPLEMENTASI KURIKULUM 2013 - Sri Murwantini (Universitas Sarjanawiyata Tamansiswa, 2017)
Principals as managers in schools, especially in vocational schools, face the challenge of changing the implementation of the 2013 curriculum. Preparedness is to recognize elements of change with open attitude, increase knowledge and skills in order to manage change so that schools become adaptive to change. This fundamental change in the 2013 curriculum is known as the element of change, which includes the Graduate Competency Standards, Content Standards, Process Standards and Assessment Standards. As the leader of change, the headmaster of SMK has a concern for the improvement of his